Evaluation of Approach to a Conspecific and Blood Biochemical Parameters in TAAR1 Knockout Mice - Ilya S. Zhukov; Maria A. Ptukha; Ekaterina A. Zolotoverkhaja; Ekaterina L. Sinitca; Ilya Y. Tissen; Inessa V. Karpova; Anna B. Volnova; Raul R. Gainetdinov (Brain Sciences, 2022)
It is known that the trace amine-associated receptor 1 (TAAR1) receptor is involved in limbic brain functions by regulating dopamine transmission and putative reward circuitry. Moreover, other TAARs are expressed in the olfactory system of all studied vertebrate species, sensing innate socially-relevant odors, including pheromones. Therefore, one can assume that TAARs may play a role in rodent social and sexual behavior. A comparative behavioral and biochemical analysis of TAAR1 knockout (TAAR1-KO) and wild-type mice is also important for the preliminary evaluation of the potential side effects of future TAAR1-based therapies. In our studies, we adapted a sexual incentive motivation test for mice to evaluate the sexual behavior of TAAR1-KO and wild-type mice. Previously, similar methods were primarily applied to rats. Furthermore, we measured testosterone and other biochemical parameters in the blood. As a result, we found only minimal alterations in all of the studied parameters. Thus, the lack of TAAR1 does not significantly affect sexual motivation and routine lipid and metabolic blood biochemical parameters, suggesting that future TAAR1-based therapies should have a favorable safety profile.